The Oxford handbook of christianity in Asia - Wilfred, Felix (Oxford handbooks, 2014)
This handbook discusses the global expansion of Christianity and the challenges it faced along the way. It is a resource for Christians and for the wider audience wanting to think more comprehensively about how Christianity was born in Asia, lost and gained ground, grew and changed across this vast of continent, and now faces many possible futures. It maps the history and current state of Christianity in Asia, providing insight into how Asian culture and its diverse religious traditions have significantly transformed Christianity to adapt to Asian life and expectations.